Analysis of Fraud on a Chinese Business Review Website - Li, Wei; Kwak, Jin Kyung (Journal of Applied Business Research, 2019)
Recently, local business-review websites have gained popularity, but the problem of fraud has become more and more severe. We did research based on the biggest Chinese local business-review website: Dazhongdianping. We collected 792,364 reviews of every registered restaurant on the Dazhongdianping website in Hangzhou, and our findings include: • Compared with US businesses Luca and Zervas (2016) who give both unfavorable reviews to their competitors and favorable reviews to their own business, Chinese businesses focus only on the latter, perhaps because of the differences in business ethics between the two countries. • Review frauds have a close relationship with the user’s social network. Users with many followers and higher interaction scores are always more powerful than other users, and they also have reasonable incentives to commit fraud. We found that these users are more likely to post fake reviews. • Finer restaurants are less likely to commit review fraud.